(untitled) (Bangladesh Journal of Otorhinolaryngology, 2025)
Background: Ludwig’s angina is a form of severe diffuse cellulitis that presents as acute onset and spreads rapidly, bilaterally affecting the submandibular, sublingual and submental spaces. Isolation of bacteria responsible for Ludwig’s angina and their antibiotic susceptibility is crucial as mixed infections are common. Objectives: To find out the microbes responsible for developing Ludwig’s angina and their antibiotic susceptibility. Methods: This cross-sectional study was conducted at Department of Otolaryngology and Head-Neck Surgery, Dhaka Medical College& Hospital, Dhaka, Bangladesh, from January 2018 to June 2019. Total 100 patients of Ludwig’s angina were enrolled. Surgical drainage followed by pus culture sensitivity was done to determine microbes responsible for Ludwig’s angina and analyzed the coverage rate of different antimicrobial agents. Results: Mean (±SD) age of the study patients was 36.83±13.7 years and majority (45%) were in 3rd decade of life with a male predominance. Dental infection was the commonest source of infection and diabetes mellitus was the major (54.0%) predisposing factor. Isolated common organisms were Streptococcus viridians (30.6%), staphylococcus aureus (25.2%), E.coli (17.1%), Pseudomonas (11.7%), Klebsiella (9.9%) and Acinetobacter (5.4%). But no organism was found in 12 cases. Maximum patients (64%) were sensitized by Ceftriaxone, Gentamycin (55%) and Ciprofloxacin (46%). However, 11 study patients developed complications. Conclusion: Ludwig’s angina is common in middle aged male. Dental infection is the commonest source of infection and diabetes mellitus is an important risk factor. Streptococcus Viridans, Staphylococcus aureus, E.coli, Pseudomonas were the common causative organism. Most effective antibiotic were Ceftriaxone, Gentamicin and Ciprofloxacin. Bangladesh J Otorhinolaryngology 2024; 30 (2): 48-57